2022
DOI: 10.3390/ijms23031642
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of an Autowave Process in a Magnetic Fluid

Abstract: Magnetic fluid (MF) is a colloidal system consisting of ferromagnetic particles (magnetite) with a diameter of ~10 nm suspended in a dispersion medium of a carrier fluid (for example, kerosene). A distinctive feature of magnetic fluid is the fact that when an electric field is applied to it using two electrodes, thin layers consisting of close-packed particles of the dispersed phase are formed in the regions near the surface of both electrodes. These layers significantly affect the macroscopic properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…One of the electrodes was transparent with respect to the falling beam. A detailed description of the experimental device and experimental technique can be found in [8,9].…”
Section: Materials and Methods: Experimental Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…One of the electrodes was transparent with respect to the falling beam. A detailed description of the experimental device and experimental technique can be found in [8,9].…”
Section: Materials and Methods: Experimental Techniquementioning
confidence: 99%
“…It was found that stable localized structures-layers in which the concentration of magnetic particles is much higher than in the rest of the solution-were formed at the boundary with the electrode [7]. This phenomenon is a distinctive feature of ferrocolloids, and near-electrode layers represent a new type of liquid membrane [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of the breakdown of the spatial charge on the transport of salt ions using formula (17) and Leveque's formula, the voltage characteristic [8][9][10][11][12][13][14][15] for the boundary value problem (1-16) is constructed and analyzed. It is shown that in the extreme current regime, the appearance of spatial charge breakdowns in the desalination channel worsens the mass transfer of salt ions: in region II (1.4-2.7 V) by 31%, in region III (2.7-3 V) by 42% (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A unique feature of ferrocolloids is the formation of dense layers of magnetite particles with a protective shell near the electrodes in a constant electric field. The layer does not mix with the main volume of the liquid and behaves as a liquid ferrocolloid membrane [7][8][9][10]. The membrane is formed as a result of electrophoresis of particles of the dispersed phase.…”
Section: Introductionmentioning
confidence: 99%